2020
DOI: 10.1186/s12889-020-8258-z
|View full text |Cite
|
Sign up to set email alerts
|

Skilled birth attendance in Sierra Leone, Niger, and Mali: analysis of demographic and health surveys

Abstract: Background: Skilled birth attendance (SBA) is a key strategy for averting maternal mortality ratio (MMR). The lifetime risk of maternal death is high in countries with low SBA. With the presence of a skilled birth attendant, the possibility of death owing to intrapartum-related complications or stillbirth can be reduced by 20%. Methods: Using data from the most recent Demographic and Health Surveys, we investigated the prevalence of skilled birth attendance, variations, and associated factors. The sample was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 24 publications
10
52
3
Order By: Relevance
“…Although the analysis did not show a significant increase in preference to home childbirth in the rural community over the urban community, still innovative strategies to increase rural community awareness on risks associated with home childbirth is highly recommended. A similar study done in Sierra Leone, Niger and Mali reported a significant relationship between rural residence and preference for home childbirth [16] The study also found that pregnant women who had higher parity were more likely to prefer home childbirth over health facility birth. Pregnant women who had two to four children were 1.5 and those who had five and above were 2.2 more likely to have home childbirth if compared to those who were pregnant for their first time.…”
Section: Discussionsupporting
confidence: 61%
“…Although the analysis did not show a significant increase in preference to home childbirth in the rural community over the urban community, still innovative strategies to increase rural community awareness on risks associated with home childbirth is highly recommended. A similar study done in Sierra Leone, Niger and Mali reported a significant relationship between rural residence and preference for home childbirth [16] The study also found that pregnant women who had higher parity were more likely to prefer home childbirth over health facility birth. Pregnant women who had two to four children were 1.5 and those who had five and above were 2.2 more likely to have home childbirth if compared to those who were pregnant for their first time.…”
Section: Discussionsupporting
confidence: 61%
“…Eighty percent of live births in the world and 59% of births in sub-Saharan Africa are attended by skilled health personnel [16]. This prevalence of SBA delivery in sub-Saharan Africa also varies across countries ranging from 13% in Nigeria to 77% in Kenya [17][18][19][20]. In Ethiopia, only 18.8 to 29.2% of births are attended by skilled health personnel [2,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to improve maternal health are constrained by inadequate skilled birth attendants and underfunding of maternal and child health [12]. Other factors obstructing progress toward improving maternal health include barriers to accessing healthcare, inadequate essential supplies, lack of emergency transport systems and poor referral services [13].…”
Section: Introductionmentioning
confidence: 99%
“…An insigni cant number of the deaths (1%) occur in the developed countries as a result of availability and accessibility of quality of care by pregnant women in the developed countries. This quality care includes skilled attendant at the delivery point [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation